RADIOCARBON IN DISSOLVED ORGANIC CARBON BY UV OXIDATION: PROCEDURES AND BLANK CHARACTERIZATION AT NOSAMS. Issue 1 (14th February 2021) - Xu, Li; Roberts, Mark L; Elder, Kathryn L; Kurz, Mark D; McNichol, Ann P; Reddy, Christopher M; Ward, Collin P; Hanke, Ulrich M
ABSTRACT: This study describes a procedural blank assessment of the ultraviolet photochemical oxidation (UV oxidation) method that is used to measure carbon isotopes of dissolved organic carbon (DOC) at the National Ocean Sciences Accelerator Mass Spectrometry Facility (NOSAMS). A retrospective compilation of Fm and δ 13 C results for secondary standards (OX-II, glycine) between 2009 and 2018 indicated that a revised blank correction was required to bring results in line with accepted values. The application of a best-fit mass-balance correction yielded a procedural blank of 22.0 ± 6.0 µg C with Fm of 0.30 ± 0.20 and δ 13 C of –32.0 ± 3.0‰ for this period, which was notably higher and more variable than previously reported. Changes to the procedure, specifically elimination of higher organic carbon reagents and improved sample and reactor handling, reduced the blank to 11.0 ± 2.75 µg C, with Fm of 0.14 ± 0.10 and δ 13 C of –31.0 ± 5.5‰. A thorough determination of the entire sample processing blank is required to ensure accurate isotopic compositions of seawater DOC using the UV oxidation method. Additional efforts are needed to further reduce the procedural blank so that smaller DOC samples can be analyzed, and to increase sample throughput.